Peningkatan Pengetahuan dan Keterampilan Kader Kesehatan dalam Pertolongan Pertama pada Kecelakaan - Yari, Yarwin; Ramba, Hardin La; Silaban, Merri; Sartika, Ikah; Rahman, Fajar Nur; Hayati, Intan Nurul (Shihatuna : Jurnal Pengabdian Kesehatan Masyarakat, 2024)
Emergency events can occur at any time, so the readiness of initial handling knowledge is an important point to prevent worsening of the patient's condition before being taken to a health facility. The general purpose of this community service is to improve people's knowledge and skills in  performing first aid in accidents. The method of implementing community service  is carried out pre-test then given Health Education and a test post is carried out regarding community knowledge and skills in performing first aid in accidents. The results of community service are respondents' knowledge related to first aid for fainting patients, bites and stings, poisoning, choking, burns and accidents, fractures before Health Education and demonstrations are on average in the sufficient and less categories, after Health Education and demonstrations the average is in the good and very good category.   The conclusion of community service is that health education with demonstration methods in conducting first aid in accidents is very effective for health cadres, as evidenced by every assessment point there is an increase in knowledge on respondents' post test scores.